Anomalous Circulation Patterns in Association with Summertime Regional Daily Precipitation Extremes over Northeast China - Chuanlei Chen; Zhaoyong Guan; Min Jiao; Pengyu Hu (Advances in Meteorology)
Based on the NCEP/NCAR daily reanalysis product, NOAA monthly sea surface temperature (SST) dataset, and daily precipitation data collected at observational stations provided by Meteorological Information Center of China Meteorological Administration, the present study analyzes characteristic circulation anomalies conducive to regional extreme daily precipitation in the summer over Northeast China. Results indicate that 26 extreme precipitation events occurred during the 36-year period of 1979–2014. The precipitation threshold for the 99th percentile is 22.2 mm/d, and the maximum extreme daily precipitation occurred in Liaoning Province. When extreme precipitation occurs, Northeast China is located to the southeast of an anomalous cyclonic circulation and northwest of an anomalous anticyclonic circulation, where a strong convergence zone is formed in the lower troposphere. The low-level convergence and upper-level divergence as well as the baroclinic circulation structure are favorable for the development of extreme daily precipitation. Meanwhile, there exist two symmetrical meridional circulations to the north and south of Northeast China. The two meridional circulations share the same ascending branch, which is conducive to the occurrence of precipitation. Located in the strong convergence zone to the southeast of the abnormal cyclonic circulation and northwest of the abnormal anticyclonic circulation, huge amounts of water vapor from the Inner Mongolia, Russia, the Japan Sea, and the mid-high latitudes of the Northwest Pacific are transported to Northeast China, providing sufficient water vapor condition for the occurrence of extreme daily precipitation in this region. In addition, daily extreme precipitation in Northeast China is also closely related to the accumulation and convergence of disturbance energy in Northeast China. It may also be related to the abnormal SST distribution that is high in the north and low in the south. Corresponding to extreme daily precipitation, SST anomaly in the Pacific Ocean is roughly characterized by the feature of “positive-north and negative- south” with the equator as the boundary.